Bioaccumulation of copper (II) and cadmium (II) from aqueous solution by pseudomonas putidamrrl B-252 - Uslu, Gülşad; Gültekin, Gülden; Tanyol, Mehtap (My University, 2011)
The bioaccumulation of copper (II) and cadmium (II) ions by viable P. putida was studied as a function of initial pH, temperature, initial glucose and initial metal ion concentration. Optimum pH value for maximum metal ion accumulation was determined to be 3.0±0.5 and 4.5±0.5 at 25 and 30 °C for each metal ion, respectively. At a constant glucose concentration, although the increase in initial copper (II) and cadmium (II) ion concentration up to approximately 25 mg L -1 increased bioaccumulation capacity of P. putida for both, all metal ion concentrations tested inhibited the growth of P. putida. High microbial growth and copper (II) and cadmium (II) accumulation yields were found at low initial metal ion concentrations. The cell and bioaccumulated metal ion concentrations and uptake yields in-creased with increasing glucose concentration up to 10 g L -1 at a constant metal ion level for each of the metal ions. Although both metal ions caused on inhibition effect on the growth of the microorganism, P. putida was capable of removing copper (II) and cadmium (II) with maximum specific uptake of 58.42 mg g -1 and 34.65 mg g -1 at 25 mg L -1 initial copper(II) and cadmium(II) level, respectively. The results also indicated that, P. putida was more efficient in accumulating larger amounts of cadmium (II) than copper (II) ions. © by PSP.
Keywords: Bioaccumulation; Cadmium(II); Copper(II); Pseudomonas putida